2018
DOI: 10.1016/j.ceca.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Key residues controlling bidirectional ion movements in Na+/Ca2+ exchanger

Abstract: Prokaryotic and eukaryotic Na/Ca exchangers (NCX) control Ca homeostasis. NCX orthologs exhibit up to 10-fold differences in their turnover rates (k), whereas the ratios between the cytosolic (cyt) and extracellular (ext) K values (K = K/K) are highly asymmetric and alike (K ≤ 0.1) among NCXs. The structural determinants controlling a huge divergence in k at comparable K remain unclear, although 11 (out of 12) ion-coordinating residues are highly conserved among NCXs. The crystal structure of the archaeal NCX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 67 publications
3
37
0
Order By: Relevance
“…We detected a Na + -dependent decrease in deuterium uptake at S int , S Ca , and S ext , but not S mid , whereas in the presence of Ca 2+ the decrease in deuterium uptake was mainly observed at S Ca . This is consistent with the predictions made by the MD simulations and mutational analyses foreseeing the occupation of S mid by a water molecule but not by Na + or Ca 2+ in the ground state (Marinelli et al, 2014;Giladi et al, 2016a;Giladi et al, 2017;van Dijk et al, 2018). Notably, subsequent crystallographic studies have validated our binding sites' assignment (Liao et al, 2016).…”
Section: Hydrogen-deuterium Exchange Mass-spectrometry Of Membrane Prsupporting
confidence: 90%
See 1 more Smart Citation
“…We detected a Na + -dependent decrease in deuterium uptake at S int , S Ca , and S ext , but not S mid , whereas in the presence of Ca 2+ the decrease in deuterium uptake was mainly observed at S Ca . This is consistent with the predictions made by the MD simulations and mutational analyses foreseeing the occupation of S mid by a water molecule but not by Na + or Ca 2+ in the ground state (Marinelli et al, 2014;Giladi et al, 2016a;Giladi et al, 2017;van Dijk et al, 2018). Notably, subsequent crystallographic studies have validated our binding sites' assignment (Liao et al, 2016).…”
Section: Hydrogen-deuterium Exchange Mass-spectrometry Of Membrane Prsupporting
confidence: 90%
“…Surprisingly, the crystal structure of NCX from Methanocaldococcus jannaschii (NCX_Mj) revealed four ion binding sites, simultaneously occupied by three Na + ions at sites termed S int , S mid , S ext , and one Ca 2+ ion at a site termed S Ca (Liao et al, 2012). Since this binding mode was inconsistent with previous studies, MD simulations and ion flux analyses of mutants were performed, suggesting that Na + ions occupy S int , S Ca , and S ext , whereas Ca 2+ occupies S Ca (Marinelli et al, 2014;Giladi et al, 2016b;Giladi et al, 2017;van Dijk et al, 2018). Thus, the Na + and Ca 2+ ions are bound in a mutually exclusive manner along the transport cycle.…”
Section: Hydrogen-deuterium Exchange Mass-spectrometry Of Membrane Prmentioning
confidence: 82%
“…The ion-binding pocket, located in the middle of the ion passageway pore, contains four putative sites (S int , S mid , S ext , and S Ca ) with distinct ion selectivity: S int and S ext exhibit high selectivity to Na + , whereas S Ca shows a similar selectivity to Na + or Ca 2+ . Follow-up studies revealed that in the OF state, NCX_Mj can bind either 3Na + (at S int , S ext , and S Ca ) or 1Ca 2+ (at S Ca ), whereas the functional role of S mid remains unclear [30][31][32][33][34][35]. The lack of the NCX_Mj crystal structure in the inward-facing (IF) state prevents the structural delineation of respective sites in the IF state.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that the prokaryotic and eukaryotic NCXs preferentially adopt the OF conformation [15][16][17][31][32][33][34], where these structure-dynamic mechanisms underlying the functional asymmetry can operate in the absence of any 'secondary' regulatory factors [36][37][38]. Previous mutational studies have identified the asymmetric contributions of distinct residues to rate-equilibrium relationships of bidirectional ion movements [31][32][33]. Consistent with these observations, the hydrogen-deuterium exchange mass spectrometry analysis of the apo-and ion-bound forms of NCX_Mj revealed that the local backbone dynamics are characteristically different at the cytosolic and extracellular vestibules [31,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation